Plasma Renin Measurements are Unrelated to Mineralocorticoid Replacement Dose in Patients With Primary Adrenal Insufficiency - GÜRAN, TÜLAY (ENDOCRINE SOC, 2020)
Context: No consensus exists for optimization of mineralocorticoid therapy in patients with primary adrenal insufficiency. Objective: To explore the relationship between mineralocorticoid (MC) replacement dose, plasma renin concentration (PRC), and clinically important variables to determine which are most helpful in guiding MC dose titration in primary adrenal insufficiency. Design: Observational, retrospective, longitudinal analysis. Patients: A total of 280 patients (with 984 clinical visits and plasma renin measurements) with primary adrenal insufficiency were recruited from local databases and the international congenital adrenal hyperplasia (CAH) registry (www.i-cah.org). Thirty-seven patients were excluded from the final analysis due to incomplete assessment. Data from 204 patients with salt-wasting CAH (149 adults and 55 children) and 39 adult patients with Addison disease (AD) were analysed. Main outcome measures: PRC, electrolytes, blood pressure (BP), and anthropometric parameters were used to predict their utility in optimizing MC replacement dose. Results: PRC was low, normal, or high in 19%, 36%, and 44% of patients, respectively, with wide variability in MC dose and PRC. Univariate analysis demonstrated a direct positive relationship between MC dose and PRC in adults and children. There was no relationship between MC dose and BP in adults, while BP increased with increasing MC dose in children. Using multiple regression modeling, sodium was the only measurement that predicted PRC in adults. Longitudinally, the change in MC dose was able to predict potassium, but not BP or PRC. Conclusions: The relationship between MC dose and PRC is complex and this may reflect variability in sampling with respect to posture, timing of last MC dose, adherence, and concomitant medications. Our data suggest that MC titration should not primarily be based only on PRC normalization, but also on clinical parameters such as BP and electrolyte concentration.
Keywords: ADDISONS-DISEASE; ANGIOTENSIN-II; DIAGNOSIS; MANAGEMENT; HYPERPLASIA; COHORT